2013
DOI: 10.1116/1.4819242
|View full text |Cite
|
Sign up to set email alerts
|

Thermal barrier coating deposition by rarefied gas jet assisted processes: Simulations of deposition on a stationary airfoil

Abstract: The uniform coating of a complex shaped substrate, such as a gas turbine airfoil, by collisionless physical vapor deposition processes requires rotation/translation of the substrate or sources and is inconceivable for regions on the substrate that are never in the line-of-sight of the vapor source. Recently developed directed vapor deposition processes use electron beam evaporation and inert gas jets to entrain, transport, and deposit metal oxide vapor in an environment where many vapor atom collisions occur p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…Both airfoils were identical in design to that used in previous studies of deposition on single airfoil substrates. 33,34 The geometry and dimensions of the 2D doublet substrate are shown in Fig. 2.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both airfoils were identical in design to that used in previous studies of deposition on single airfoil substrates. 33,34 The geometry and dimensions of the 2D doublet substrate are shown in Fig. 2.…”
Section: Methodsmentioning
confidence: 99%
“…[41][42][43] Both the DSMC simulation method, and its application to the simulation of vapor deposition have been described in detail elsewhere. 15,33,44 The simulation grid used here for the a ¼ 0 substrate orientation is shown in Fig. 4.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, a second order central scheme with boundedness has been used for spatial discretization in quasi-DNS. In addition, Rodgers et al [53], simulated the deposition process by using direct simulation monte carlo (DSMC) method. Sreedharan et al [54] found that LES calculations were sensitized to temperature and ash composition for syngas ash deposition in the hot gas path.…”
Section: Solution To Turbulent Flowmentioning
confidence: 99%